Actividades turísticas como estrategia de inclusión social dirigido al turismo social gerontológico - JUSTILLO DIAZ, CARMEN LISBETH (2024)
The present case study is titled tourist activities as a social inclusion strategy aimed at gerontological social tourism where its objective is to analyze the tourist activities that function as a social inclusion strategy in the Ventanas canton. For this, a non-experimental cross-sectional research was used, with a quantitative approach because the data was collected and analyzed from a survey which allowed capturing the perception of older adults about their participation in tourist activities, it was also used as a population, older adults residing in the canton, where a non-probabilistic convenience sampling was applied, which allowed the participants to be chosen in a non-random manner, using specific criteria such as convenience, availability or accessibility, thus the sample was made up of 20 adults. older people from the town of the Ventanas canton. Which allowed us to make some recommendations such as investigating and promoting new tourism proposals for older adults in the canton of Ventanas whose local leaders and tourism service providers could collaborate in the search for cultural tourism options, soft ecotourism and recreational activities adapted to preferences. and capabilities of this group of people.